Comparative study between injection parecoxib and butorphanol for postoperative analgesia in laparotomy patients - Fating, Dnyaneshwar R.; Tirpude, N. G. (International Journal of Research in Medical Sciences, 2017)
Background: Pain is a complex, subjective experience comprising both physical and emotional components. Upper abdominal surgeries cause most intense pain and distress. Opioids and Nonsteroidal anti-inflammatory drugs are used for postoperative analgesia. Aim of this study was to compare the efficacy of analgesia between injection parecoxib and butorphanol. Methods: Prospective randomised comparative study included total 60 patients posted for laparotomy under general anaesthesia. Patients were randomly allocated in two groups. One group received injection paecoxib sodium (Group-P) and other group received injection Butorphanol (Group- B) half an hour before extubation. Pain score was recorded as per visual analogue scale at 0, 4,8,12 hours. The side effects if any were recorded and vomiting and sedation score was recorded. Results: Immediately in postoperative period VAS was less in Group B, but at 8 hours. VAS was less in Group P. Conclusions: Parecoxib has better quality of pain relief, minimal side effects compared to butorphanol which has good analgesia in immediate postoperative period.